A regional computable general equilibrium model for Guatemala: Modeling exogenous shocks and policy alternatives - Morley, Samuel; Piñeiro, Valeria (International Food Policy Research Institute, 2011)
In this paper we develop a dynamic regional computable general equilibrium (CGE) model for Guatemala that incorporates regional disaggregated sectors for agriculture. The model is designed to be useful as a development tool for determining the effects of regional investments intended to reduce regional poverty and also to explore policy options to deal with a number of macro and balance-of-payments issues. Our model extends previous modeling work on Guatemala in several ways. First, it develops an updated regional social accounting matrix (SAM) for 2008, coupled with an updated CGE. Second, the CGE is a recursive dynamic model that incorporates unemployment in the short run. Most CGE models are not useful for short-run analysis because they are comparative static models that assume full employment. We specify a fixed minimum wage and an informal sector and use a recursive dynamic framework to solve for the short-run adjustment process that occurs as the economy responds to shocks. Second, the model is regional, permitting us to examine the impact of sectoral development policies, particularly those focused on agriculture. Guatemala has one of the lowest investment rates in Latin America. We show that if the investment share is raised by 4percent over five years, the rate of growth of the economy rises by about .6 percentage points. Guatemala is also quite sensitive to external macro disturbances. Our dynamic model gives a first approximation of the timing and nature of the adjustment over the ten years following various macro disturbances. We show that after ten years most of these shocks are absorbed by changes in the real exchange rate and the composition of output rather than the rate of growth of output. Negative shocks cause a real devaluation and a shift from consumption and non-tradables and towards exports and tradable goods. An important empirical question is whether the adjustment toward the traded goods sector is as flexible as the underlying elasticities in the model imply.